EVALUATION OF FOOD MANAGEMENT FOR PATIENTS IN THE NUTRITION DEPARTMENT OF MALAHAYATI ISLAMIC HOSPITAL, MEDAN - Ritonga, Futri; Berutu, Mastuti; Tambunan, Siti Soraya; Tanjung, Vindy Ammadhea; Kinanti, Widya; Tanjung, Nadia Ulfa (HEARTY, 2025)
Hospitals function as healthcare service facilities for the community and have characteristics influenced by several factors, including advancements in medical science, technological progress, and the socio-economic conditions of the population. This study aims to evaluate the management of the food service system in the nutrition department for patients at Malahayati Islamic Hospital in Medan. This research employs a qualitative descriptive approach, utilizing data collection techniques through direct observation and interviews with food service staff. The results indicate that the food procurement system at Malahayati Islamic Hospital, from ordering and purchasing to receiving, storing, and distributing food ingredients, complies with hospital food service standards (PGRS). However, improvements are needed in food processing, presentation, and distribution, specifically in monitoring and evaluating the washing of food ingredients before chopping and the use of personal protective equipment (PPE) by serving staff. This study was conducted to enhance awareness and concern regarding their responsibilities.